Pengaruh Opini Audit, Tipe Pemerintah Daerah, Umur Administratif, dan Kekayaan Daerah terhadap Praktik Internet Financial Reporting (IFR) dalam Website Pemerintah Daerah: Studi Empiris pada Kabupaten/Kota di Sumatra Tahun Anggaran 2024 - Afrian, Muhammad; Nelvirita, Nelvirita (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to examine the influence of audit opinion, type of local government, administrative age, and regional wealth on the practice of internet financial reporting (IFR) on local government websites. This is a causative research study. The population and sample consist of the financial reports of regency and city governments in Indonesia for the year 2024. The sampling technique used is purposive sampling. The type of data employed is secondary data. Data collection was conducted through documentation methods by collecting local government financial reports and reviewing each local government’s official website. The data analysis method used is multiple regression analysis, with internet financial reporting as the dependent variable and audit opinion, type of local government, administrative age, and regional wealth as independent variables. The results of the study indicate that audit opinion, type of local government, and administrative age do not have a significant effect on the practice of internet financial reporting on local government websites, whereas regional wealth has a negative effect on the practice of internet financial reporting.